Anodic oxidation of sulfamethoxazole paired to cathodic hydrogen peroxide production. (April 2023) - Ali, Izba; Barros de Souza, Allisson; De Laet, Steven; Van Eyck, Kwinten; Dewil, Raf
Abstract: A double chamber electrochemical system is developed consisting of a boron-doped diamond (BDD) anode and a graphite cathode, which not only degrades sulfamethoxazole (SMX) but also simultaneously generates hydrogen peroxide ( H 2 O 2 ). The degradation of SMX is carried out by (in)direct oxidation at the BDD anode and H 2 O 2 is produced by two electron oxygen ( O 2 ) reduction reaction (ORR) at the cathode. The effect of different parameters on the kinetics of both mechanisms was investigated. The performance of the system at the optimized conditions (pH 3, 0.05 M N a 2 S O 4 as electrolyte, and 10 mA as applied current) showed that after 180 min of electrolysis, SMX was almost fully degraded (95% removal and ∼90% COD reduction) as well as about 535 μM H 2 O 2 was accumulated. With the help of LC-MS, five intermediates formed during SMX electrolysis were properly identified and a degradation pathway was proposed. This study advocates methods for improving the effectiveness of energy use in advanced wastewater treatment. Graphical abstract: Image 1 Highlights: Electrochemical oxidation of sulfamethoxazole at a BDD anode was studied. Optimal conditions for H 2 O 2 production at a graphite cathode were investigated. The system enables sulfamethoxazole degradation and simultaneous H 2 O 2 production. Transformation products were identified, and the degradation pathway was proposed.